EVALUATION OF PROJECT COST AND TIME USING EARNED VALUE APPROACH: A CASE OF MILITARY INFRASTRUCTURE PROJECT - Nazaruddin Nazaruddin; Laksono Djoko Nugroho; Haris Muhammadun (Pusat Publikasi Nusantara, 2025)
This research aims to optimize the performance of construction projects at Yohanis Kapiyau Airbase so that the work can be completed on time, meet quality standards, and in accordance with the predetermined budget. This research addresses key questions regarding the evaluation of project cost and time control, specifically examining project cost performance through Cost Variance and Cost Performance Index (CPI) indicators, as well as project time performance using Schedule Variance (SV) and Schedule Performance Indices (SPI) indicators. The implementation of the Earned Value Management (EVM) method has proven its effectiveness as an analytical instrument that integrates cost and cost dimensions comprehensively. Through the comprehensive analysis that has been conducted, the method successfully identified with precision that the fundamental challenge of the project lies in the aspect of time management, while cost management shows excellent efficiency. It can be concluded that the achievement of excellent cost efficiency has a positive impact on the overall project performance. Based on the results of the comprehensive evaluation, several strategic recommendations can be formulated for the optimization of project implementation in the future.